3 - Beyond Recrimination: The Rule of Law and Nigeria’s Anti-graft War - Albert, Isaac Olawale (Africa Development, 2019)
The existing literature on corruption in Nigeria and several other parts of the world focuses exclusively on recrimination, namely the securitisation or demonisation of the people accused of corruption and privileging the need to punish them. Atomised in these extant studies is the fact that anti-graft regimes equally have the responsibility to protect the rights of these accused persons in line with the principle of the rule of law. Refusal to protect these rights constitutes a form of corruption in itself. This article considers this issue as crucial to the assessment of the anti-graft war in Nigeria, since 2015 when Muhammadu Buhari became the president of the country. Attention is called to three of the nagging rule of law issues in the country seeking to be actionably addressed: (i) the abusive manner in which some of the accused persons are apprehended; (ii) how they are subjected to ‘media trial’ though the government eventually loses many of the celebrated cases; and (iii) how the Federal Government disobeys court orders to release some of the accused persons. This questions the credibility of the ongoing anti-graft war in the country and casts an air of authoritarianism around the regime of President Muhammadu Buhari. What Nigeria needs at this moment, in its democratisation effort, is an anti-corruption process that is based on the rule of law. Suggestions are made on how to deal with some of the emerging issues.